Effect of Bentonite on Fibrinolytic System in Serum - Olesen, E. S (Thrombosis and Haemostasis, 1963)
Treatment of serum with bentonite led to a reduced content of inhibitors of trypsin and urokinase in the isoelectrically precipitated euglobulin, and removed fibrinolytic agents and precursors from serum. Bentonite-treated serum added to untreated serum reduced precipitation of the above inhibitors, and presumably also precipitation of inhibitors against a plasminogen activator of serum.Bentonite-treated serum (whether from pig, ox, guinea-pig, or man), added to untreated guinea-pig serum, produced fibrinolytic activity on isoelectric precipitation of the mixture; the activity of the euglobulin was due to an activator of plasminogen as well as an active protease, probably plasmin. The described effects of bentonite-treated serum are similar to those previously reported for anionic polyelectrolytes. Possible mechanisms are discussed.The “non-specific” activation of fibrinolytic activity by means of bentonite emphasizes that guinea-pig serum [which is characterized by a high potential for “nonspecific” activation of its fibrinolytic system Olesen (1962)] contains all the elements required for the formation of an activator of plasminogen, and thus the activation of its plasminogen to plasmin.